Thermal and moisture transport in fibrous materials - Pan, N. (Ning); Gibson, Phil (Woodhead publishing in textiles., 2006)
The transfer of heat and moisture through textiles is vital to the manufacture and design of clothing, technical and protective textiles. Continued advances in textile processing technology, the growth of manufactured nonwovens and the application of nanotechnology have resulted in a wealth of research in order to characterise the behaviour of these materials. Thermal and moisture transport in fibrous materials provides a comprehensive guide of the technological developments and scientific understanding in this area. The first section summarises the structure, geometry and stereology of fibrous materials. The fundamentals of wetting and its dynamics are also discussed. Part two analyses thermal and liquid interactions in textiles and offers insights into the thermodynamic behaviour of moisture as well as heat and moisture coupling. The book concludes with chapters on the human thermoregulatory system, interfacing between fibrous materials and the human body and innovative computer modelling simulations. Thermal and moisture transport in fibrous materials is an essential reference for all those involved in the textile industry, especially those concerned with the design and manufacture of technical textiles and protective clothing. Summarises the structure, geometry and stereology of fibrous materialsDiscusses the fundamentals of wetting and its dynamicsAnalyses thermal and liquid interactions in textiles.